(untitled) - Ireland, Sue (Cambridge, 2010)
This short course includes 40-50 hours of essential exam practice, tips and strategies to prepare students for the Cambridge ESOL PET examination. PET Direct prepares students for the Cambridge ESOL PET examination. The Student's Book contains 12 topic-based units, providing 40-50 hours of core material, and can be used as either a short intensive course or to accompany a general English course. The accompanying CD-ROM includes a full practice test, a step-by-step guide to the exam and the audio for the practice test included in the Workbook.
Keywords: English language,Tiếng Anh; Examinations, questions, etc.,Kỳ thi, câu hỏi